Gyanyin goddess: two bronze figures - two different stories - Kajdański, Edward (Art of the Orient, 2014)
The first of these stories is connected with the name of Kazimierz Grochowski (1873 - 1937), the forgotten Polish geologist, archeologist, traveller and writer, to whom I owe my long-standing interest in the history of East Asia. He was a director of the Polish Gymnasium in Harbin (North-East China, Manchuria at that time) where I was born and where I received my secondary and high-school education. Grochowski also used to teach us the history and geography of the Far East and was a patron of our Polish Oriental Circle (Polskie Koło Wschodoznawcze), which he established in the frame of his educational work. I would like to recall a short outline of his biography. [...]